1217. Staphylococcus Protein A (spa) Typing Demonstrates Genetic Heterogeneity of Methicillin-Susceptible Staphyloccus aureus (MSSA) in a Neonatal Intensive Care Unit (NICU). (26th November 2018) - Hill-Ricciuti, Alexandra; Ferguson, Samantha; Geng, Wenjing; Stump, Stephania; Messina, Maria; Zachariah, Philip; Sahni, Rakesh; Green, Daniel; Whittier, Susan; Saiman, Lisa; Uhlemann, Anne-Catrin
Abstract: Background: In the NICU, MSSA is a more prevalent pathogen than MRSA, but optimal infection prevention and control strategies for MSSA are not yet well understood. There are likely multiple routes of MSSA acquisition given its role as normal flora and its detection in the anovaginal tract of pregnant women. We describe the molecular epidemiology of MSSA in our NICU during a yearlong surveillance effort. Methods: Included infants were hospitalized in a university-affiliated level III-IV NICU from January to December 2017 (1032 admissions) and had positive clinical and/or surveillance cultures for MSSA. Infants admitted at ≥7 days of age were screened for MSSA colonization by culturing the anterior nares and three skin sites. All infants in the NICU were screened twice monthly. Spa typing was performed to genetically characterize isolates. Results: During the study period, MSSA was identified in 187 infants (18 at admission, 145 by twice monthly surveillance, and 24 from clinical cultures). In all, 269 MSSA isolates (245 surveillance and 24 clinical isolates) from 166 infants were spa typed. Sixty-two MSSA spa types were identified; 31 (50%) were each detected in only one infant. The incidence of the nine most common spa types is shown (Figure 1); t279 (13%), t002 (8%), and t1451 (6%) had the highest incidence. t1451 and t571 belong to ST398, a common MSSA clone in the local community. The epidemiology of spa types varied; e.g., incident cases of t279 was detected in 10 months, t1451 was detected in 6 months and t148 in 3 months. Among the 14 sets of twins and triplets with MSSA isolates, 12 (86%) shared the same spa type as their sibling(s). Of the 58 infants with >1 MSSA isolate, 12 (21%) acquired new spa-types. No spa type(s) predominated in the 19 episodes of invasive infections. In 6 infants with both colonizing and invasive isolates, colonizing and invasive isolates were the same spa type(s) in 5. Conclusion: Spa typing demonstrated that MSSA isolates in our NICU exhibited substantial genetic heterogeneity. While these data do not elucidate acquisition route(s), they suggest infants are acquiring MSSA from multiple sources, likely including family members and the local community. Ongoing sequencing studies are examining common spa types to further understand transmission dynamics. Disclosures: A. C. Uhlemann, Merck: Investigator, Grant recipient